Minimally Invasive Total Arterial Bypass Grafting via Left Mini-thoracotomy in Obese Patients - Gadelkarim, Ibrahim; Shaqu, Rakan; Kang, Jagdip; Zakhary, Waseem; Dashkevich, Alexey; Ender, Jörg; Waha, Sussane de; Borger, Michael; Verevkin, Alexander (The Thoracic and Cardiovascular Surgeon, 2025)
Minimally invasive cardiac surgery total arterial coronary artery bypass grafting (MICS-CABG) has emerged as an alternative to conventional coronary artery bypass grafting (CABG). Its safety and efficacy in obese patients remain a concern due to technical challenges. The current study compares early and long-term outcomes of MICS-CABG in obese and non-obese patients.Between January 2015 and December 2023, 279 patients underwent off-pump MICS-CABG at our center. Obesity was defined as body mass index ≥30 (kg/m2). The primary endpoint was 30-day survival. Secondary endpoints were survival and freedom from major adverse cardiac and cerebrovascular events (MACCE) at 5 years.Of all 279 patients, 56 (20.1%) were classified as obese and 223 (79.9%) as non-obese. Obese patients had a higher EuroSCORE II (2.06 ± 1.53 vs. 1.63 ± 0.94, p = 0.008) and a higher prevalence of comorbidities including diabetes mellitus (p < 0.001) and pulmonary hypertension (p = 0.03). The incidence of postoperative complications including repeat thoracotomy for bleeding (p = 0.18), low cardiac output syndrome (p = 0.70), or wound infection (p = 0.38) did not differ between obese and non-obese patients. There were no deaths or myocardial infarctions within 30 days in obese patients (0% vs. 0.5%, p = 0.95; 0% vs. 2.7%, p = 0.47). Long-term outcome at 5 years, including survival (91.9% vs. 92.4%, p = 0.99) and freedom from MACCE (83.3% vs. 84.6%, p = 0.63), showed no difference between the two groups.MICS-CABG can be performed safely and efficaciously in select obese patients by specialized coronary surgeons at high-volume cardiac centers.
Keywords: minimally invasive surgery (includes port access mini-thoracotomy); coronary artery bypass grafts surgery; CABG; obesity